Morphology, Mineralogy and Chemistry of an Ex-Mining Land in Ipoh, Perak - Jusop, Shamsuddin; Nik Wan, Nik Mokhtar; Paramananthan, S. (1986)
A study was carried out to characterize the 20.3 ha of ex-mining land at Kg. Kepayang Baru, Ipoh. The study shows that the ex-mining land can be classified into three groups i. e., sandy, clayey and a mixture of sandy and clayey deposits. The bases, organic carbon, phosphorus and nitrogen contents are very low. The cation exchange capacity is low, but pH is very high. The dominant minerals in the clay fraction are kaolinite, mica and chlorite.